Identification of tumors with NRG1 rearrangement, including a novel putative pathogenic UNC5D-NRG1 gene fusion in prostate cancer by data-drilling a de-identified tumor database - Ptáková, Nikola; Martínek, Petr; Holubec, Luboš; Janovský, Václav; Vančurová, Jana; Grossmann, Petr; Navarro, Paloma Alcaraz; Rodriguez Moreno, Juan F; Alaghehbandan, Reza; Hes, Ondřej; Májek, Ondřej; Pešek, Miloš; et al. (Genes, chromosomes & cancer, 2021)
The fusion genes containing neuregulin-1 (NRG1) are newly described potentially actionable oncogenic drivers. Initial clinical trials have shown a positive response to targeted treatment in some cases of NRG1 rearranged lung adenocarcinoma, cholangiocarcinoma, and pancreatic carcinoma. The cost-effective large scale identification of NRG1 rearranged tumors is an open question. We have tested a data-drilling approach by performing a retrospective assessment of a de-identified molecular profiling database of 3263 tumors submitted for fusion testing. Gene fusion detection was performed by RNA-based targeted next-generation sequencing using the Archer Fusion Plex kits for Illumina (ArcherDX Inc., Boulder, CO). Novel fusion transcripts were confirmed by a custom-designed RT-PCR. Also, the aberrant expression of CK20 was studied immunohistochemically. The frequency of NRG1 rearranged tumors was 0.2% (7/3263). The most common histologic type was lung adenocarcinoma (n = 5). Also, renal carcinoma (n = 1) and prostatic adenocarcinoma (n = 1) were found. Identified fusion partners were of a wide range (CD74, SDC4, TNC, VAMP2, UNC5D), with CD74, SDC4 being found twice. The UNC5D is a novel fusion partner identified in prostate adenocarcinoma. There was no co-occurrence with the other tested fusions nor KRAS, BRAF, and the other gene mutations specified in the applied gene panels. Immunohistochemically, the focal expression of CK20 was present in 2 lung adenocarcinomas. We believe it should be considered as an incidental finding. In conclusion, the overall frequency of tumors with NRG1 fusion was 0.2%. All tumors were carcinomas. We confirm (invasive mucinous) lung adenocarcinoma as being the most frequent tumor presenting NRG1 fusion. Herein novel putative pathogenic gene fusion UNC5D-NRG1 is described. The potential role of immunohistochemistry in tumor identification should be further addressed.
Keywords: dospělí; Antigens, Differentiation, B-Lymphocyte; HER; membránový protein 2 asociovaný s vezikuly; receptor tyrosine kinase; Adult; Histocompatibility Antigens Class II; neuregulin-1; nádory plic; ERBB3; fúzní onkogenní proteiny; NRG1; gene fusion; genetics; lidé; next-generation sequencing; HER 3; mRNA sequencing; Oncogene Proteins, Fusion; nádory prostaty; Aged, 80 and over; MAPK; Prostatic Neoplasms; Syndecan-4; EGF-like domain; gene rearrangement; lung; antigeny diferenciační B-lymfocytární; molecular; syndekan-4; Tenascin; Adenocarcinoma; Male; Aged; adenokarcinom; receptory buněčného povrchu; ERBB; Neuregulin-1; tenascin; data drilling; Lung Neoplasms; Vesicle-Associated Membrane Protein 2; PIK; receptor heterodimerization; Receptors, Cell Surface; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; MHC antigeny II. třídy; neuregulin; Middle Aged; carcinoma; Humans